Microbiological Quality, Shelf Life and Fermentation Activity of Active Dried Yeast - Simpson, Estelle; Tracey, R.P. (South African Journal of Enology and Viticulture, 2017)
The microbiological quality and shelf life of 10 active dried yeast preparations were determined. The dried yeasts were tested for total microbial count, total yeast count, total wild yeast count, total bacterial count, spore forming bacteria, Enterobacteriaceae and lactic acid bacteria. For the shelf life test, the yeasts were stored at 0°C, 4°C, 15°C and 25°C for six months and tested at monthly intervals for total viable yeast count and total bacterial count. After six months storage fermentations were carried out in Colombar must and the wines subsequently analysed. All dried yeasts complied with the International Wine Office ( 0 .I. V.) guideline of 1 x 109 viable yeasts per gram dried yeast, whilst only some preparations complied with the guideline for total bacterial count of 1 x 105 bacteria per gram dried yeast. Results of the shelf life test showed optimum storage temperature to be 4°C.